Antifungal effect of Quillaja saponaria plant extract on biofilms of five Candida species of dental interest - Bessa, Ellen Roberta Lima; Muniz, Ana Bessa; Ramos, Lucas de Paula; Oliveira, Luciane Dias de (Brazilian Dental Science, 2024)
Objective: The objective of this study was to evaluate the action of Q. saponaria glycolic extract on the biofilms of standard strains of C. albicans, C. glabrata, C. krusei, C. dubliniensis, and C. tropicalis. Material and Methods: Monomicrobial biofilms of the five Candida species were grown for 48 h, followed by treatment with the isolated extract at five concentrations (100 mg/mL, 50 mg/mL, 25 mg/mL, 12.5 mg/mL, and 6.25 mg/mL) and two times of exposure to treatment in all groups (5 min and 24 h), the untreated group, and the group treated with 0.12% chlorhexidine (CLX). To analyze cell viability, the MTT test was used, and the optical densities were transformed into a percentage of metabolic activity. In statistical analysis, data were analyzed by ANOVA and Tukey’s test, considering a significance level of 5%. Results: The biofilms, when analyzed after a time of 5 minutes, showed fungal reduction when exposed to treatments at 5 concentrations of Quilaia extracts when compared to the untreated group. This applies to the species of C. albicans, C. glabrata, C. krusei, and C. dubliniensis (p<0.0001), as only the biofilms formed by C. tropicalis, despite providing reduction, did not show significant differences between the groups. At 5 minutes, only the biofilms of C. albicans, C. grabrata, and C. krusei treated with Quilaia extract 100 mg/mL showed superior and significant results compared to the group treated with CLX, but at a concentration of 50 mg/mL, only group C. albicans. Within 24 h, all groups and all concentrations of Quilaia demonstrated antifungal action (p<0.0001). Despite showing a reduction greater than or similar to that promoted by CLX in 24 hours when comparing concentrations of 100 mg/mL and 50 mg/mL, the C. albicans groups showed statistically significant differences in this comparison and at this time (p<0.0001). Conclusion: Therefore, Quilaia extract demonstrated high antifungal potential and was capable of acting on the reduction of Candida spp. biofilms at both treatment exposure times and concentrations. KEYWORDS Candida; Quilaia; Phytotherapy; Biofilm; Plant extracts.